IMAJINASI VISUAL TAJEN DALAM FOTOGRAFI EKSPRESI - I Komang Adi Kusuma; I Made Saryana; Putu Agus Bratayadnya (Retina Jurnal Fotografi, 2021)
Bali is one of the provinces in Indonesia which has a variety of unique arts, cultures and customs. From the various kinds of arts, culture and customs in Bali, it is inseparable from Hindu religious activities in general in Bali. One of them is cockfighting or commonly called tajen. Cockfighting is one of the cultures of the Hindu community in Bali to offer blood as a ritual in Hinduism known as tabuh rah. The author uses Expression Photography in realizing this work, because he wants to show tajen from a different angle and wants to be more free to explore, express, imagine, the author's experience related to the tajen phenomenon in Bali. Through digital processing, which is controlled by the author with Photoshop software, objects can be manipulated, adding or subtracting objects in order to get a work that has a maximum visual appearance. To further strengthen this, the author utilizes the theoretical basis of aesthetics and semiotics in photographic works and maximizes visual elements in photographic works. The data used in this work are secondary data and primary data. The creator's data collection process uses a qualitative method, which is a method used to observe the environment and the documentation method through digital photo camera recordings, which is then followed by image processing on computer software. The process of observing the creation of this work is done by observing objects related to the making of Expression Photography before taking a photo. At the shooting stage, data collection is also carried out on the angle of shooting / camera angle against the object and the angle of light on the object. So that the resulting photo has charm and beauty. Keywords: Tajen, Expression Photography, Art, Culture and Custom